Penerapan Desain Pada Permainan Anak Berkebutuhan Khusus - Nadilla Ramadhita (Institut Seni Indonesia Yogyakarta, 2018)
In daily life at least there is one product that we use to support our activities, ranging from clothing, cutlery, transportation, toiletries, games, and so forth. So also children who have limitations or special needs. In everyday life they also need a game that is able to stimulate their brain and motor. Design as a science that can meet the needs of these children has a very important role in this regard. As the times progress, children's games have designs that can meet the needs of their users. Key words: product, diffable, game, motoric, design